2023
DOI: 10.1038/s41526-023-00315-x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for plant biology in space and analogue environments

Veronica De Micco,
Giovanna Aronne,
Nicol Caplin
et al.

Abstract: Advancements in plant space biology are required for the realization of human space exploration missions, where the re-supply of resources from Earth is not feasible. Until a few decades ago, space life science was focused on the impact of the space environment on the human body. More recently, the interest in plant space biology has increased because plants are key organisms in Bioregenerative Life Support Systems (BLSS) for the regeneration of resources and fresh food production. Moreover, plants play an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…There are several concerns of growing plants in space, and there is much still unknown. Unique concerns to growing plants in space is exposure to ionizing radiation, which could alter gene expression, and microgravity, which severely alters plant physiology (Vandenbrink and Kiss, 2016;De Micco et al, 2023). A study found that secondary metabolite production of Cannabis was enhanced in a simulated microgravity setting (Darigh et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%
“…There are several concerns of growing plants in space, and there is much still unknown. Unique concerns to growing plants in space is exposure to ionizing radiation, which could alter gene expression, and microgravity, which severely alters plant physiology (Vandenbrink and Kiss, 2016;De Micco et al, 2023). A study found that secondary metabolite production of Cannabis was enhanced in a simulated microgravity setting (Darigh et al, 2022).…”
Section: Future Directionsmentioning
confidence: 99%